Task Technology-Fit of a Village Financial System (Siskeudes) to Increase Officers’ Performance - Michael Musyaffi , Ayatulloh; Muna, Arinal (KnE Social Sciences, 2020)
Village Financial System (Siskeudes) is an information system that assists village governments in reporting financial reports transparently and accountably. On the other hand, Siskeudes cannot be optimal, moreover various problems found in this system such as the delay of financial reporting and error recording. One of the factors of the problems is the incompatibility of tasks in operating the application. This study aims to analyze the causes and consequences of task mismatches by using task technology-fit model. The respondents in this research are thirty village officers who used Siskeudes from eleven villages in Cirebon. This study was analyzed using questionnaires and in-depth interviews. The method of this study used Partial Least Square (PLS) using SmartPls 3.0. Moreover, the results of this study indicated that task of the technology-fit model had a significant influence on Performance Impact. Villages that had tasks that are in accordance to Siskeudes operations, in this case the finance department who had a knowledge in the financial sector) had better levels of performance. However, the task characteristics do not have a significant effect on task technology-fit because task characteristic of the government are based on the regulations and the law. Keywords: Performance Impact, Task Characteristic, Task Technology-Fit, Village Financial System